Factors that prolong the ‘postmortem interval until finding’ (PMI-f) among community-dwelling elderly individuals in Japan: analysis of registration data - Ito, Tomoko; Tamiya, Nanako; Takahashi, Hideto; Yamazaki, Kentaro; Yamamoto, Hideki; Sakano, Shoji; Kashiwagi, Masayo; Miyaishi, Satoru (BMJ Open, 2012)
Objectives To clarify the factors affecting ‘postmortem interval until finding’ (PMI-f) among elderly unexpected death cases. Design Cross-sectional study. Setting All area of Yamagata prefecture in Japan. Participants Entering subjects were 5675 elderly cases with age of ≥65 years selected from all 9002 cases of unexpected death from 2002 to 2007 in Yamagata prefecture between 2002 and 2007. Our final study subjects consisted of 3387 cases sampled with several criteria to assess the factors to prolong PMI-f. Primary outcome measures The outcome was the postmortem interval until finding (PMI-f) as the time from death until finding the body which we defined in this study. Results ‘Living alone’ showed the highest adjusted HR (3.73, 95% CI 3.37 to 4.13), also ‘unnatural death’ (1.50, 1.28 to 1.75), ‘found at own home’ (1.37, 1.22 to 1.55) and ‘younger subjects’ (0.99, 0.98 to 0.99). In the model including interactions with the household situation, we found ‘male subjects living alone’ and ‘female subjects living with family’ tended to be found later. Conclusions PMI-f is an effective outcome for quantitative analyses of risk of bodies left. To prevent the elderly dead bodies left for long time, it is necessary to keep regular home-based contact with elderly individuals living alone.